Stress, Anxiety and Depression among Introverts and Extroverts: A Comparative Study - Azam, Hooria; Fatima, Radaf; Afzal, Huria; Saleem, Tamkeen (Pakistan Journal of Humanities and Social Sciences, 2024)
The primary aim of this current research endeavor was to undertake a comprehensive examination of Depression, Anxiety, and Stress levels within the distinct contexts of introverts and extroverts. The study adopted a methodological approach rooted in Cross sectional research design in current research study. Convenient sampling strategically was employed to gather data from 100 university students from universities of twin cities of Rawalpindi and Islamabad, Pakistan. The selection of participants was contingent upon their identification as either introverts or extroverts, and this stratification sought to elucidate nuanced differences in psychological well-being. To collect the data, two key measurement instruments were administered to the participants, Depression Anxiety Stress Scale (DASS-21) was utilized to quantify the levels of Depression, Anxiety, and Stress, while the Introversion Scale (IS- 18) facilitated the categorization of individuals as either introverts or extroverts. For data analysis Statistical Package for Social Sciences (SPSS) was used, and the scores of independent sample T test, showed no statistically significant differences in the levels of Depression, Anxiety, and Stress between individuals classified as introverts and those identified as extroverts